Social norms and prejudice against homosexuals - Pereira, A.; Monteiro, M. B.; Camino, L. (The Spanish Journal of Psychology, 2009)
Different studies regarding the role of norms on the expression of prejudice have shown that the anti-prejudice norm influences people to inhibit prejudice expressions. However, if norm pressure has led to a substantial decrease in the public expression of prejudice against certain targets (e.g., blacks, women, blind people), little theoretical and empirical attention has been paid to the role of this general norm regarding sexual minorities (e.g., prostitutes, lesbians and gays). In this sense, the issue we want to address is whether general anti-prejudice norms can reduce the expression of prejudice against homosexual individuals. In this research we investigate the effect of activating an anti-prejudice norm against homosexuals on blatant and subtle expressions of prejudice. The anti-prejudice norm was experimentally manipulated and its effects were observed on rejection to intimacy (blatant prejudice) and on positive-negative emotions (subtle prejudice) regarding homosexuals. 136 university students were randomly allocated to activated-norm and control conditions and completed a questionnaire that included norm manipulation and the dependent variables. A multivariate analysis of variance (MANOVA) as well as subsequent ANOVAS showed that only in the high normative pressure condition participants expressed less rejection to intimacy and less negative emotions against homosexuals, when compared to the simple norm-activation and the control conditions. Positive emotions, however, were similar both in the high normative pressure and the control conditions. We concluded that a high anti-prejudice pressure regarding homosexuals could reduce blatant prejudice but not subtle prejudice, considering that the expression of negative emotions decreased while the expression of positive emotions remained stable.